Ole G. Mouritsen: Seaweeds, Edible, Available & Sustainable - Bird, Fi (Petits Propos Culinaires, 2013)
Ole G. Mouritsen: Seaweeds, Edible, Available & Sustainable: University of Chicago Press, 2013: 272 pp., hardback, £24.50.